PENGEMBANGAN MODUL PEMBELAJARAN PADA MATERI BILANGAN BULAT DAN PECAHAN UNTUK MENINGKATKAN MINAT BELAJAR SISWA - Buulolo , Siwika (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2023)
The purpose of this research is to develop learning modules that are valid, practical and effective, and can increase students' interest in learning. This type of research is development research with a 4D model, namely Define, Design, Develop and Disseminate. The data analysis technique in this study is validity, practicality and effectiveness analysis. The results of module validation by the validator average value of 3.31 "very valid" (82.75%), student responses to the practicality of the module average value of 4.01 "practical" (80.2%), student learning interest after module to the effectiveness of the module average value of 4.50 "very effective" (90%), and the results of increasing learning interest increased 35.8% from initial learning interest with an average value of 2.71 (54.2%) while the final average -average value of 4.50 (90%).